A unified model of student engagement in classroom learning and classroom learning environment: one measure and one underlying construct - Cavanagh, Rob (Kluwer Academic Publishers, 2015)
This study employed the capabilities-expectations model of engagement in classroom learning based on bio-ecological frameworks of intellectual development and flow theory. According to the capabilities-expectations model, engagement requires a balance between the capabilities of a student for learning in a particular situation and what is expected of that student’s learning. The study also used an eight-element model of the classroom learning environment (self educational values, self learning outcomes, classroom/peer learning attitudes and behaviours, classroom/peer support, classroom/peer discussion, classroom planning, teacher support and expectations, and parental involvement). The aim was to test the assumption that engagement in classroom learning and perceptions of the classroom learning environment both indicate the same uni-dimensional construct. If this assumption is correct, then it should be possible to plot measures of student engagement and measures of the learning environment on the same linear scale. A measurement model such as the Rasch Model can then be used to test how well empirical data fit the scale. An 85-item rating scale survey of student engagement in classroom learning and the classroom learning environment scale was created. Data from its administration to 1760 secondary school students were tested for fit to the Rasch Rating Scale Model. Data on engagement in classroom learning and the classroom learning environment were able to be plotted on one interval scale, therefore suggesting the presence of the underlying common construct. The construct was called an engaging learning environment.